Email
logo

Ask Questions, Get Answers

X
 
Questions  >>  CBSE XI  >>  Math  >>  Sequences and Series
Answer
Comment
Share
Q)

Find the sum of $n$ terms of the series whose $n^{th}$ term is $(2n-1)^2$

$\begin{array}{1 1}\large\frac{n(4n^2-5)}{3} \\\large\frac{n(4n^2+1)}{3} \\\large\frac{n(4n^2-1)}{3} \\\large\frac{n(4n^2-n-1)}{3} \end{array} $

1 Answer

Comment
A)
Toolbox:
  • Sum of $n$ terms of any series $=S_n=\sum t_n$
  • $\sum (A+B)=\sum A+\sum B$
  • $\sum k.A=k.\sum A$ where $k$ is a constant.
  • $\sum n^2=\large\frac{n(n+1)(2n+1)}{6}$
  • $\sum n=\large\frac{n(n+1)}{2}$
  • $\sum 1=n$
Given $t_n=(2n-1)^2=4n^2-4n+1$
We know that sum of $n$ terms of the series $=S_n=\sum t_n=\sum(4n^2-4n+1)$
$\Rightarrow\:S_n=4\sum n^2-4.\sum n+\sum 1$
$\qquad\:=4.\large\frac{n(n+1)(2n+1)}{6}$$-4.\large\frac{n(n+1)}{2}$$+n$
$\qquad\:=n\bigg[\large\frac{2(n+1)(2n+1)}{3}$$-2(n+1)+1\bigg]$
$\qquad\:=n\bigg[\large\frac{4n^2+6n+2-6n-6+3}{3}\bigg]$
$\qquad\:=\large\frac{n(4n^2-1)}{3}$
Help Clay6 to be free
Clay6 needs your help to survive. We have roughly 7 lakh students visiting us monthly. We want to keep our services free and improve with prompt help and advanced solutions by adding more teachers and infrastructure.

A small donation from you will help us reach that goal faster. Talk to your parents, teachers and school and spread the word about clay6. You can pay online or send a cheque.

Thanks for your support.
Continue
Please choose your payment mode to continue
Home Ask Homework Questions
Your payment for is successful.
Continue
...